Trigeminal Nerve Control of Cerebral Blood Flow: A Brief Review - White, Timothy G.; Powell, Keren; Shah, Kevin A.; Woo, Henry H.; Narayan, Raj K.; Li, Chunyan (Frontiers in Neuroscience, 2021)
The trigeminal nerve, the fifth cranial nerve, is known to innervate much of the cerebral arterial vasculature and significantly contributes to the control of cerebrovascular tone in both healthy and diseased states. Previous studies have demonstrated that stimulation of the trigeminal nerve (TNS) increases cerebral blood flow (CBF) via antidromic, trigemino-parasympathetic, and other central pathways. Despite some previous reports on the role of the trigeminal nerve and its control of CBF, there are only a few studies that investigate the effects of TNS on disorders of cerebral perfusion (i.e., ischemic stroke, subarachnoid hemorrhage, and traumatic brain injury). In this mini review, we present the current knowledge regarding the mechanisms of trigeminal nerve control of CBF, the anatomic underpinnings for targeted treatment, and potential clinical applications of TNS, with a focus on the treatment of impaired cerebral perfusion.